Production of smart nanocomposite for glass coating toward photochromic and long-persistent photoluminescent smart windows. Issue 1 (1st January 2022) - Al-Qahtani, Salhah D.; Binyaseen, Adel M.; Aljuhani, Enas; Aljohani, Meshari; Alzahrani, Hanan K.; Shah, Reem; El-Metwaly, Nashwa M.
Abstract: Novel photoluminescent surface coatings were developed for simple industrial production of fluorescent photochromic and persistent photoluminescent smart materials. The photochromic fluorescent coatings are able to emit light of different color underneath an irradiation light supply, while the persistent phosphorescent coatings are able to continue the emission of light for an extended time period even after removing the irradiation light source. Photoluminescent lanthanide-doped strontium aluminum oxide (LSAO) immobilized into polystyrene (PS) nanocomposite coatings for glasses were developed by ultrasonic-assisted solution blending approach. To achieve a complete transparency for the produced coatings, the nanoparticle form of LSAO was well-dispersed in the PS matrix. LSAO nanoparticles were characterized by TEM, and the morphologies were reported on SEM, X-ray fluorescence (XRF) and EDX. The uncoated, pigment-free and photoluminescent coated glasses were colorless under normal visible daylight. Only luminescent coatings displayed bright green at lower concentrations of LSAO and bright white at higher concentrations of LSAO under ultraviolet lamp. Greenish-yellow color was also monitored in the dark for luminescent coatings. The prepared smart glasses displayed absorbance intensity at 355 nm and two emission bands at 425 and 508 nm. Both photoluminescence spectra and mechanical properties of the generated smart glasses were analyzed to display better resistance to scratching and superhydrophobic activity, compared to the uncoated glass, without adversely influencing their inherent spectral characteristics. The photoluminescent spectral studies demonstrated both photochromic fluorescent and long-persistent phosphorescent properties. The enhancement in scratch resistance and superhydrophobic properties of coated glasses can be attributed to inclusion of LSAO in polystyrene matrix. Compared to uncoated glass sample, the produced PS-LSAO nanocomposite coatings demonstrated ultraviolet protection, high durability, photostability and high reversible responsiveness to UV light without fatigue. Thus, PS-LSAO nanocomposite coatings can be applied onto a glass surface for various industrial purposes, such as solar panels, optical devices and architectural applications.